INFLUENCE OF TRUST, QUALITY OF SERVICE, AND WORD OF MOUTH ON THE DECISION TO USE THE SERVICES LION PARCEL SERVICE (Case Study on Lion Parcel Pos Charity Company) - Anggiat Sinaga; Amin Hou; Eka Martyna Theodora; Suwandy Purba; Elisa Oktavia Simatupang (SEAN Institute, 2022)
The research approach used is descriptive research with a quantitative approach. The location of this research was carried out at Lion Parcel Pos Amal, which is located at Jl. Charity No. 27 district. Medan Sunggal, Medan, North Sumatra. The population in this study were all customers who had delivered goods at Lion Parcel Mitra Pos Amal with a sample of 120 people/customer. The sampling technique in this study used an accidental sampling technique. This study uses primary and secondary data. The result of this research is that trust has a positive effect on the decision to use Lion Parcel services. Service quality has a positive effect on the decision to use Lion Parcel services. Word of Mouth partially has a positive effect on the decision to use the services of Lion Parcel. Determination Test Results that Trust, Service Quality, and word of mouth have contributed to the decision to use Lion Parcel services by 83.1% while the remaining 16.9% is influenced by other variables outside this regression model.